The Effect of Enterprise Risk Management on Financial Performance of Insurance Companies in Indonesia - Hilda Nurasyifa; Franciskus Antonius Alijoyo (Yayasan Riset dan Pengembangan Intelektual, 2026)
The increasingly complex business environment has heightened the importance of effective risk management practices, particularly in the insurance industry, which is inherently exposed to various financial and operational risks. Enterprise Risk Management (ERM) has emerged as a comprehensive framework that enables organizations to identify, assess, monitor, and manage risks in an integrated manner across all business functions. Previous studies have shown that ERM contributes to improved firm value, profitability, operational performance, and organizational resilience. However, empirical evidence regarding the impact of ERM on the financial performance of insurance companies in Indonesia remains limited. Therefore, this study aims to examine the effect of Enterprise Risk Management on the financial performance of insurance companies in Indonesia. This study employs a quantitative research approach using panel data obtained from annual reports and audited financial statements of insurance companies listed in Indonesia during the period 2020–2024. Enterprise Risk Management is measured using the Enterprise Risk Management Disclosure Index (ERMDI), while financial performance is measured using Return on Assets (ROA). Firm size and leverage are included as control variables. Panel data regression analysis is employed to test the relationship between ERM and financial performance. The findings indicate that Enterprise Risk Management has a positive and significant effect on financial performance. Insurance companies with higher levels of ERM implementation tend to achieve better profitability due to stronger risk governance, improved internal control systems, more efficient resource allocation, and enhanced decision-making processes. Furthermore, firm size positively influences financial performance, while leverage has a negative effect. This study contributes to the growing literature on Enterprise Risk Management and provides practical implications for insurance companies seeking to improve financial performance through the implementation of integrated risk management practices.